Huseyn Baykaro skills in public adminstration and politics but olso in the management of literary processes in khazoin ul maoni - Isroilov, G`ayrat (FILOLOGIYA UFQLARI JURNALI, 2023)
Huseyn Baykaro skills in public adminstration and politics but olso in the management of literary processes in khazoin ul maoni